Translative Linguistics: an Aspectualized Review of Initial Provisions. Part 1. Gnoseology of Translation - Golev, N. D. (Вестник Кемеровского государственного университета, 2022)
The article introduces translative linguistics as a special branch in the study of natural languages and describes the history of its development. Translative linguistics uses the methods of quantitative linguistics, combinatorial linguistics, associative grammar, lexicography, etc. It focuses on the same aspects of language as historical grammar, phonetics, political linguistics, etc. The ontology of translational linguistics sees the natural language and its units as its research object. Translation (reserve translation, machine translation, and reverse machine translation) acts as a research method that translational linguistics uses to describe the patterns of the translated language. The author reviews various scientific publications to describe the concepts and terms of translational linguistics. The author uses the method of linguistic logic, which is understood as incorporating a new concept in the traditional system of theoretical linguistic concepts.